2012
DOI: 10.1051/radiopro/2012011
|View full text |Cite
|
Sign up to set email alerts
|

Environmental risk assessment of radon from ceramic tiles

Abstract: Radon-222 exhalation from different ceramic tiles depends upon the radium ( 226 Ra) concentration and porosity. Raw zirconium sand is one of the substances widely used in the ceramic industry and it is naturally radioactive. This can produce unjustified concern and subsequently perturb the market of these products. The radon exhalation rates for all ceramic tile companies were in the ranges 28-44 mBq.m -2 .h -1 and 2.0 to 4.8 mBq.kg -1 .h -1 . The porosity of ceramic tiles is in the range 0.19-0.28. The radium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
(9 reference statements)
0
8
0
Order By: Relevance
“…Table 1 indicates that the concentration of radon gas in the buildings with ceramic flooring had the maximum value compared to other types of flooring. The results of a study by Majed et al ( 43 ) showed that the materials used in the manufacture of ceramic materials are the main sources of radon in closed spaces. The radon emissions of the industrial ceramics manufactured in 13 Egyptian plants were 668 ± 68 Bq/m 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 indicates that the concentration of radon gas in the buildings with ceramic flooring had the maximum value compared to other types of flooring. The results of a study by Majed et al ( 43 ) showed that the materials used in the manufacture of ceramic materials are the main sources of radon in closed spaces. The radon emissions of the industrial ceramics manufactured in 13 Egyptian plants were 668 ± 68 Bq/m 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Mirghafoori et al (2014) evaluated various risks occurring during the manufacturing process in the ceramic industry; the authors only considered manufacturing-related risks instead of overall supply chain risks. Maged et al (2012) discussed the environmental risk associated with the ceramic industry. Masum and Johora (2012) evaluated the performance and financial stability of Bangladeshi ceramic industry, and Jahan (2010) discussed the competitive environment of the ceramic sector of Bangladesh.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Besides, due to the increased percentage of high LET particles, radiobiological characteristics of the beam may also change with the depth [Ghergherehchi, et al, 2008]. Maged et al investigated both of the environmental risk assessment of radon from ceramic tiles in Egypt, estimating the radon concentration in water and indoor air and radon concentration in elementary schools in Kuwait by using CR-39 track detectors [28][29][30] [Maged, et al, 2012;Maged, 2009 andMaged, 2006]. Our studies were extended to include the track density, the track dimension, orientation and roundness response of alpha particles from 241 Am source of energy ~5.5 MeV and from alpha particles emitted from radon exposure since 1997 via sharing in radon Intercomparison [EUR, 1998] as shown in Tables 2-3.…”
Section: (C)mentioning
confidence: 99%